Menakar Eksistensi Guru: Antara Konsep dan Realita dalam Standar Proses Pembelajaran - Uang , Yulinda (Jurnal Pendidikan Islam Indonesia, 2018)
Education produced quality generations, whether formal or informal. The mandate of Law No. 20 of 2003 states that Education was a conscious and planned effort to create an atmosphere of learning and learning process so that learners actively develop their potential to have strength spiritual, self-control, personality, intelligence, noble character, and skills which is needed them and society. The author analyse there was a gap in the process of applying the curriculum. Keep in mind the geographical, cultural and access in different regions of Indonesia, it becomes an obstacle in the education service. The results obtained that students' understanding of school. The subject matter was weak. At the moment the teacher's role was only as a symbol that carried out teaching assignments in the classroom, without evaluating whether his or her students can understand what has been said? Teachers were only trying to live out what the government has set, but those who accepted the risks are scholars as receiving education.